2015
DOI: 10.1027/2151-2604/a000227
|View full text |Cite
|
Sign up to set email alerts
|

Salzburger State Reactance Scale (SSR Scale)

Abstract: Abstract. This paper describes the construction and empirical evaluation of an instrument for measuring state reactance, the Salzburger State Reactance (SSR) Scale. The results of a confirmatory factor analysis supported a hypothesized three-factor structure: experience of reactance, aggressive behavioral intentions, and negative attitudes. Correlations with divergent and convergent measures support the validity of this structure. The SSR Subscales were strongly related to the other state reactance measures. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…We also found that control-averse behavior was accompanied by negative affects ( Dillard and Shen, 2005 ) and the motivation to restore one's freedom of choice ( Brehm, 1966 ; Miron and Brehm, 2006 ). This is consistent with previous research on reactance that has focused on behavioral intentions in hypothetical scenarios ( Sittenthaler et al, 2015 ) or behavior in nonsocial settings ( Chartrand et al, 2007 ). Our study complements and extends this research by providing evidence of the motivation to act against the restriction of one's freedom of choice during social decisions with actual consequences.…”
Section: Discussionsupporting
confidence: 91%
“…We also found that control-averse behavior was accompanied by negative affects ( Dillard and Shen, 2005 ) and the motivation to restore one's freedom of choice ( Brehm, 1966 ; Miron and Brehm, 2006 ). This is consistent with previous research on reactance that has focused on behavioral intentions in hypothetical scenarios ( Sittenthaler et al, 2015 ) or behavior in nonsocial settings ( Chartrand et al, 2007 ). Our study complements and extends this research by providing evidence of the motivation to act against the restriction of one's freedom of choice during social decisions with actual consequences.…”
Section: Discussionsupporting
confidence: 91%
“…Building on the classic measure of reactance, that is, the decrease in attractiveness of an imposed option (Brehm, 1966; Brehm and Brehm, 1981), we assessed participants’ ratings of the initiative’s actions. To provide another measure of reactance, we used items of the validated Salzburger State Reactance Scale (SSR Scale; Sittenthaler et al, 2015). On a scale ranging from 1 ( not at all ) to 5 ( very much/strong ), participants evaluated their current experience of reactance ( α = 0.90, seven items, M = 2.33, SD = 0.69, e.g., “To what extent do you perceive the implementation of the initiative as a restriction of freedom?”) and behavioral intentions ( α = 0.80, four items, M = 1.88, SD = 0.92, e.g., “How strong is your desire to complain about the implementation to the curricular committee?”).…”
Section: Methodsmentioning
confidence: 99%
“…We randomly assigned participants to the voluntary ( n = 32) or mandatory ( n = 33) condition. As in Study 1, we afterward assessed participants’ experience of reactance and behavioral intentions (Sittenthaler et al, 2015; experience of reactance: M = 1.93, SD = 0.70; α = 0.85; behavioral intentions: M = 1.47, SD = 0.49; α = 0.71).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for the possibility that the peer effects on control-averse behavior might be moderated by subjects’ general tendency to rebel against restrictions of their freedom of choice, we asked subjects to fill in a German version of the Hong Psychological Reactance Scale (HPRS) 19,20,36 . The HPRS consists of 14 items that describe general attitudes and habits.…”
Section: Methodsmentioning
confidence: 99%